Mapping Communication Infrastructure Theory Onto Twitter: Network Integration and Neighborhood Storytelling. - ZHENG AN; MENDIOLA-SMITH, LUANA (International Journal of Communication (19328036), 2018)
Guided by communication infrastructure theory (CIT), this study examined residents' integration to the neighborhood storytelling network and its association with neighborhood storytelling. The ego networks of the local ties of 350 residents and their timelines were obtained from Twitter's search application programming interface (API). Residents' integration to the neighborhood storytelling network was operationalized as network size and network density. The results show that both network size and network density positively predicted neighborhood storytelling. When local ties were classified into types, residents who followed more geo-ethnic media accounts and other local residents participated more in neighborhood storytelling.